Existence and Explanation
XII, 247 p.
Keywords: This collection of essays is dedicated to 'Joe' Karel Lambert. The contributors are all personally affected to Joe in some way or other, but they are definitely not the only ones. Whatever excuses there are - there are some -, the editors apologize to whomever they have neglected. But even so the collection displays how influential Karel Lambert has been, personally and through his teaching and his writings. The display is in alphabetical order - with one exception: Bas van Fraassen, being about the earliest student of Karel Lambert, opens the collection with some reminiscences. Naturally, one of the focal points of this volume is Lambert's logical thinking and (or: freed of) ontological thinking. Free logic is intimately connected with description theory. Bas van Fraassen gives a survey of the development of the area, and Charles Daniels points to difficulties with definite descriptions in modal contexts and stories. Peter Woodruff addresses the relation between free logic and supervaluation semantics, presenting a novel condition which recovers desirable metatheoretic properties for free logic under that semantics. Terence Parsons shows how free logic can be utilized in interpreting sentences as purporting to denote events (true ones succeed and false ones fail) and how this helps to understand natural language.